2017
DOI: 10.1097/qai.0000000000001497
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Translating PrEP Interest Into Uptake in an Observational Study of Young Black MSM

Abstract: Background HIV incidence among US young, black MSM (YBMSM) is high, and structural barriers (e.g. lack of health insurance) may limit access to Pre-Exposure Prophylaxis (PrEP). Research studies conducted with YBMSM must ensure access to the best available HIV prevention methods, including PrEP. Methods We implemented an optional, non-incentivized PrEP program in addition to standard HIV prevention services in a prospective, observational cohort of HIV-negative YBMSM in Atlanta, GA. Provider visits and lab co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 31 publications
5
67
3
Order By: Relevance
“…We found that African American individuals in Mississippi had a significantly lower prevalence of retention in care compared to white individuals at initial and long‐term follow‐up visits. Previous research has found significant racial disparities in PrEP uptake and other PrEP care continuum endpoints , as well as across the HIV care continuum . Racial differences in retention in care were observed in our previous study among a similar population, where the follow‐up period was attenuated at the six‐month endpoint .…”
Section: Discussionsupporting
confidence: 59%
“…We found that African American individuals in Mississippi had a significantly lower prevalence of retention in care compared to white individuals at initial and long‐term follow‐up visits. Previous research has found significant racial disparities in PrEP uptake and other PrEP care continuum endpoints , as well as across the HIV care continuum . Racial differences in retention in care were observed in our previous study among a similar population, where the follow‐up period was attenuated at the six‐month endpoint .…”
Section: Discussionsupporting
confidence: 59%
“…Willingness to use PrEP grew in the sample overall, and in all demographic groups except MSM of multiple races, men recruited through geospatial social networking apps, and men with certain types of health insurance. The reasons that men who are aware of PrEP are not willing to take it are varied, and have been reported to include concerns about side effects, concerns about drug resistance, low perception of risk for HIV, aversion to daily pill taking, and low perceived efficacy of PrEP . Taken together, these data suggest that additional educational efforts could address some of the reasons for unwillingness to take PrEP that are less subjective.…”
Section: Discussionmentioning
confidence: 98%
“…As the rates of new infections continue at alarming rates among specific key populations, e.g. transgender persons in Europe and the U.S. and Black MSM in the U.S., and these populations face numerous social, structural, and economic barriers to accessing PrEP and being retained in PrEP care [125], any efforts at implementing PrEP must be culturally-tailored to engage and support these individuals and must address persistent inequities (table 2). …”
Section: Discussionmentioning
confidence: 99%